Development of Civil Engineering Management Models Based on Community Participation: A Scoping Review in Timor Leste - Francisco Da Conceição Neves De Sousa; Lalu Mulyadi; Foury Handoko; Nanta Sigit (International Journal of Business and Quality Research, 2026)
Infrastructure development plays a crucial role in promoting economic growth and social welfare, particularly in developing countries such as Timor Leste. However, infrastructure projects in such contexts often face technical, managerial, and social challenges that limit their effectiveness and sustainability. One of the key issues identified is the limited integration of community participation within civil engineering management practices. This study aims to systematically map and analyze existing literature on participatory-based civil engineering management models for infrastructure development through a scoping review approach. This research adopts a qualitative scoping review methodology following established review frameworks to identify, select, and synthesize relevant peer-reviewed studies published over the past decade. Academic databases including Google Scholar, Scopus, and ScienceDirect were used to retrieve literature focusing on civil engineering management, community participation, and infrastructure development in developing countries. The selected studies were analyzed thematically to identify key trends, model components, and research gaps. The findings indicate that although community participation is widely recognized as an important factor in enhancing project relevance, sustainability, and social acceptance, its implementation within civil engineering management remains fragmented and largely confined to the planning stage. Moreover, existing models tend to emphasize technical and managerial efficiency while insufficiently integrating participatory and social dimensions. In the context of Timor Leste, these limitations are further compounded by institutional capacity constraints and post-conflict governance challenges. This study concludes that there is a critical need for a comprehensive and context-sensitive civil engineering management model that integrates technical rigor with meaningful community participation across all stages of infrastructure development. The results of this scoping review provide a conceptual foundation for future empirical research and offer practical insights for policymakers and practitioners aiming to achieve inclusive and sustainable infrastructure development in Timor Leste and similar developing country contexts.